Incidence, clinical presentation, and outcome of progressive multifocal leukoencephalopathy in HIV-infected patients during the highly active antiretroviral therapy era: a nationwide cohort study - Engsig, Frederik Neess; Hansen, Ann-Brit Eg; Omland, Lars Haukali; Kronborg, Gitte; Gerstoft, Jan; Laursen, Alex Lund; Pedersen, Court; Mogensen, Christian Backer; Nielsen, Lars; Obel, Niels (The Journal of infectious diseases, 2009)
Human immunodeficiency virus (HIV) infection predisposes to progressive multifocal leukoencephalopathy (PML). Here, we describe the incidence, presentation, and prognosis of PML in HIV-1-infected patients during the period before highly active antiretroviral therapy (HAART) (1995-1996) and during the early HAART (1997-1999) and late HAART (2000-2006) periods. Patients from a nationwide population-based cohort of adult HIV-1-infected individuals were included. We calculated incidence rates of PML and median survival times after diagnosis. We also described neurological symptoms at presentation and follow-up. Among 4,649 patients, we identified 47 patients with PML. The incidence rates were 3.3, 1.8, and 1.3 cases per 1000 person-years at risk in 1995-1996, 1997-1999, and 2000-2006, respectively. The risk of PML was significantly associated with low CD4(+) cell count, and 47% of cases were diagnosed by means of brain biopsy or polymerase chain reaction analysis for JC virus. The predominant neurological symptoms at presentation were coordination disturbance, cognitive defects, and limb paresis. Thirty-five patients died; the median survival time was 0.4 years (95% confidence interval [CI], 0.0-0.7) in 1995-1996 and 1.8 years (95% CI, 0.6-3.0) in both 1997-1999 and 2000-2006. CD4(+) cell count >50 cells/microL at diagnosis of PML was significantly associated with reduced mortality. The incidence of PML in HIV-infected patients decreased after the introduction of HAART. Survival after PML remains poor. In the management of PML, the main focus should be on prophylactic measures to avoid immunodeficiency.